Experimental investigation of wear of multiwalled carbon nanotube particles-filled poly-ether-ether-ketone matrix composites under dry sliding. (April 2019) - Kumar, D; Rajmohan, T
Polymer matrix composites have revealed enormous potential to substitute metal components in a wide variety of applications because of their self-lubrication properties, lightweight and resistance to wear, corrosion and organic solvents. However, additional upgrading in their properties is still essential. The endeavour of this research was to assess the effect of the material type and the morphology of multiwalled carbon nanotubes (MWCNTs) on the wear performance of poly-ether-ether ketone (PEEK) matrix composites. The MWCNT-filled PEEK matrix composites were prepared using melt mixing technique. The wear behaviour of reinforced MWCNT-filled PEEK composites was studied using the pin-on-disc apparatus under dry sliding conditions at different applied loads, sliding speeds, temperature and wt% MWCNTs. Experiments were conducted using response surface methodology (RSM)-based central composite design. The specific wear rate and coefficient of friction were considered as wear performances of MWCNT-filled PEEK matrix composites. The second-order models are developed to optimize the wear parameters using the genetic algorithm technique. The morphologies of the worn surfaces were observed by scanning electron microscopy.